Performance of the EarlyCDT® Lung test in detection of lung cancer and pulmonary metastases in a high-risk cohort. (August 2021) - Borg, Morten; Wen, Sara W.C.; Nederby, Line; Hansen, Torben Frøstrup; Jakobsen, Anders; Andersen, Rikke Fredslund; Weinreich, Ulla Møller; Hilberg, Ole
Highlights: EarlyCDT® Lung test was tested in a high-risk cohort with an assay sensitivity of 33 %. Assay sensitivity was 11 % in patients below 60 years of age. Assay sensitivity was 21 % in stage I-II lung cancer patients. EarlyCDT® Lung and CT screening criteria combined detected 17 % of lung cancer cases. We find insufficient sensitivity of the EarlyCDT® Lung as part of screening criteria. Abstract: Objectives: Early detection of lung cancer is pivotal for an optimal prognosis. CT screening is currently implemented in USA. To decrease the amount of CT scans, the application of a blood-based biomarker as part of screening criteria is desirable. Materials and methods: The EarlyCDT® Lung test was performed in a high-risk cohort composed 246 patients referred from their GP on suspicion of lung cancer. Blood samples were taken at first visit and patients underwent diagnostic workup on suspicion of lung cancer resulting in either a malignant diagnosis or ruled out cancer. Sensitivity and specificity of the EarlyCDT® Lung were calculated in the cohort and subgroups based on age, smoking history, sex and lung cancer stage. Results: Overall sensitivity in the cohort was 33 % for lung cancer and 31 % for primary lung cancer and lung metastases combined. Sensitivity in age groups was 11 % (60 years or below), 31 % (61−75 years) and 55 % (>75 years). In patients with at least 10 tobacco pack years, sensitivity was 33 % while the sensitivity in patients with at least 50 tobacco pack years was 44 %. The assay sensitivity in stage I-II lung cancer patients was 21 %, while this was 40 % in stage III-IV lung cancer patients. In a subgroup of patients that met current CT screening criteria (age 55–80 years and minimum 30 tobacco pack years) the sensitivity was 37 %. Conclusion: The rationale of screening for lung cancer is to find patients in an early and resectable stage. However, the EarlyCDT® Lung test performed best in elderly, late stage lung cancer patients with a heavy smoking history. Based on these results, the current study finds insufficient sensitivity of the EarlyCDT® Lung test to be used as part of inclusion criteria in a low-dose CT program for detection of lung cancer.